Tecnologias leves e enfermagem em unidades de terapia intensiva : um estudo comparativo - Marinho, Pabliane Matias Lordelo (2015)
Lightweight technologies relate to the binding process of patient health professionals, to the empowerment of the individual, to welcoming and the management of assistance focused on the demands of the patient. The nursing staff, to be next to the patient during the 24 hours, is predisposed to the use of these technologies, especially in intensive care units, where attention is intended to meet continuous vulnerability of patients. General objective: to compare the use of lightweight technologies in the care provided by nursing in intensive care units between public hospitals, being a State education and another in the city of Aracaju/SE. Method: descriptive, cross-sectional study of quantitative approach and observational nature. The data were collected by means of an observation instrument validated through the Percentage of Agreement and Content Validity Index (CVI) by six judges from December 2014 and February 2015. The data were collected in the teaching Hospital and State Hospital during the period of March and April 2015, in which were observed nurses and nursing assistants/technicians for assistance activities. In the analysis of the data has been used the Kolmorogov-Smirnov test, Mann-Whitney Test and Chi-square. Results: the Kolmorogov-Smirnov test showed the non-normal distribution of light technologies and the Mann-Whitney Test presented a p-value < 0.0001 which means that the use of lightweight technology by State and teaching Hospital were statistically different, being that the teaching Hospital showed the highest prevalence in the use of light technologies. As for the professional category, the nurses used most often lightweight technologies technicians/nursing assistants. Conclusion: lightweight technologies, when used effectively, transform the process of work, impacting on the humanization in nursing care, since the essence of care is the human being and the application of such technologies lead to a rapprochement with other needs in addition to the biological.